Assessing the impact of urinary incontinence on quality of life: systematic review of instruments in Portuguese. - Wolpe, Raquel Eleine; Toriy, Ariana Machado; Silveira, Gabriella Franzoni da; Cardoso, Fernando Luiz; Sperandio, Fabiana Flores (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Urinary incontinence (UI) can have a large impact on quality of life (QOL), which can harm social, economic, psychological and sexual aspects. Instruments are used to assess such damages. As it comes to subjective information, questionnaires are suitable tools to measure these variables. OBJECTIVE: To identify the instruments used to assess the impact of urinary incontinence on quality of life and evaluate them regarding the psychometric properties. METHOD: A search for articles that used specific questionnaires to assess the impact of urinary incontinence on QOL was conducted using the following descriptors: urinary incontinence, questionnaire, quality of life, in English, Portuguese and Spanish in the following databases: PubMed, SciELO and Scopus, then the validation of questionnaires in Portuguese (Brazil) to classify them as to the process of cross-cultural adaptation and psychometric properties. RESULTS: Seven questionnaires were found: International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF), International Consultation on Incontinence Questionnaire - Overactive Bladder (ICIQ-OAB), Overactive Bladder Questionnaires (OAB-q), OAB-q generated the short form (OAB-q SF), Urinary Incontinence - Specific Quality of Life Instrument (I-QOL), King’s Health Questionnaire (KHQ) and Qualiveen. Only KHQ, ICIQ-SF and ICIQ-OAB followed all the steps of cultural adaptation. ICIQ-OAB and I-QOL showed higher number of assessed and certified psychometric properties. None of the studies showed results on responsiveness, “floor or ceiling” effects and interpretability. CONCLUSION: The data collected in this review showed that the instrumentation of UI is being made incomplete and is not respecting the prerequisite of the completion of steps in the process of creation and testing, possibly compromising an effective assessment of quality of life